Traditional Chinese medicine for the treatment of diabetic kidney disease: A study-level pooled analysis of 44 randomized controlled trials - Liu, Xuele; Ge, Minyao; Zhai, Xinyu; Xiao, Yang; Zhang, Yaheng; Xu, Ziling; Zhou, Zhiguang; Mei, Zubing; Yang, Xuejun (Frontiers in Pharmacology, 2022)
Background Accumulating evidence suggests that traditional Chinese medicine (TCM) has significant effects on reducing 24-hour urinary protein (24-h UPRO) and improves renal function indices. The current evidence is still not enough due to the limitation of clinical center size and sample size. Objective We aimed to update the current evidence on the efficacy of TCM in the treatment of diabetic kidney disease (DKD). Methods PubMed, Embase, the Cochrane Library and SinoMed were searched to identify randomized controlled trials (RCTs) comparing the clinical efficacy of TCM combined with Western medicine with that of Western medicine alone for the treatment of DKD. The main outcome measure was 24-h UPRO. The secondary outcomes were serum creatinine (Scr), blood urea nitrogen (BUN), glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), total cholesterol (TC) and triglyceride (TG). Pooled analyses were performed using random-effects models. Results A total of 44 RCTs with 3730 participants were included. The summary estimates showed that compared with Western medicine alone, TCM combined with Western medicine significantly improved 24-h UPRO (standardized mean difference (SMD) -1.10, 95% confidence interval (CI) -1.45 to -0.74). Moreover, TCM combined with Western medicine significantly reduced the levels of other renal function indices, including Scr (SMD -1.25, 95% CI: -1.69 to -0.81) and BUN (SMD -0.75, 95% CI: -1.10 to -0.40). TCM combined with Western medicine also showed greater benefits in reducing the levels of FBG (SMD -0.31, 95% CI: -0.47 to -0.15) and HbA1c (SMD -0.62, 95% CI: -0.89 to -0.36) in patients with DKD. In addition, superior effects on the lipid profile were noted in the TCM combined with Western medicine group in terms of TG (SMD -1.17, 95% CI: -1.76 to -0.59) and TC (SMD -0.95, 95% CI: -1.43 to -0.47). The risk of bias could have resulted from selective reports, unclear randomization methods, unblinded assignments, and some missing data. Conclusion The results of this meta-analysis suggest that TCM combined with Western medicine has significant effects on reducing 24-h UPRO and improves renal function indices and lipid profiles compared with Western medicine alone for DKD.